Involvement of Imam in The Legality of Unregistered Marriages in The Bajo Tribe Society Kepulauan Riau - Nuraida; Aris Bintania; Arbisora Angkat; Asrizal Saiin (Mir'ah: Family Law and Legal Culture, 2024)
The practice of unregistered marriages is still common, one of which is performed by the Bajo tribe in Kepulauan Riau. However, there is something that attracts attention when the participation of an imam is used as a label to validate the marriage. This research uses qualitative descriptive research. The data obtained included primary and secondary data obtained by going directly to the field for interviews. The results of this research show that there is a unique way to perform the practice of unregistered marriage performed by the Bajo tribe in Kepulauan Riau so that it is considered legal, namely by visiting the house of one of the Imams who has been appointed outside the area as the person performing the marriage, although they do not know the name and its origin. For the Bajo society in Kepulauan Riau, a marriage cannot take place without an imam. Therefore, this marriage has no legal protection for children and wives. Although the traditions of a society must be maintained, in terms of the legality of marriage, it is non-negotiable, but every marriage must still be registered. In Islam, the concept of marriage registration is a form of renewal in the field of Islamic family law.